Adequate and safe operative fixation of ankle fractures by residents and orthopedic trauma surgeons - Van Vehmendahl, Robyn; van Silfhout , Lysanne; Tiel Groenestege, Dieuwertje; Pull ter Gunne, Albert; Bemelman, Michael; Edwards, Michael; Nelen, Stijn; Smeeing, Diederik (Journal of the Foot & Ankle, 2025)
Objective: Investigate surgical outcomes of patients with ankle fractures operated on by residents and orthopedic trauma surgeons. Methods: Retrospective cohort study including all adult patients surgically treated for ankle fracture from 2016 to 2020 in regional hospitals in the Netherlands. Data regarding patient demographics, fracture characteristics, and treatment characteristics were collected from patient medical records. Results: Patient demographics and fracture characteristics were similar for patients who underwent surgery by residents compared to those operated on by orthopedic trauma surgeons. There was no significant difference in postoperative complications, revision surgeries (2.8% vs. 4.7%), surgery duration (60.0 minutes vs. 54.0 minutes), or quality of life for residents compared to orthopedic trauma surgeons. Differences were seen in surgical treatment, with external fixation (2.2% vs. 5.2%), medial screw fixation (21.4% vs.28.5%), and dorsal plate fixation (21.4% vs. 28.5%) being significantly more often used in patients operated on by surgeons. Logistic regression showed that primary surgeon being a resident or orthopedic trauma surgeon was not a predictor for complications. Conclusion: Outcomes after surgical fixation of ankle fractures are comparable for residents and orthopedic trauma surgeons. Careful selection of patients combined with an appropriate level of supervision is necessary for residents to develop their skills without putting patients at risk. Level of evidence: Level II, Prognostic study, Retrospective study.